Pertussis-like syndrome or pertussis: a delay diagnosis - Heda Melinda Nataprawira; Finia Cahayasari; Arifin Kashmir (Indonesian Pediatric Society, 2012)
Background Recent reports of pertussis epidemiology from Asia,Africa and South America have been limited, but the WorldHealth Organization estimates indicate that these regions havethe highest disease burden. Difficulty in estimating the prevalenceof pertussis is due to lack of access to diagnostic methods,misdiagnoses, under-reporting, and different countries' reportingcriteria. A syndrome characterized by severe episodes of coughingresembling whooping cough (pertussis) has also been defined aspertussis-like syndrome.Objective To report eleven cases of pertussis or pertussis-likesyndrome in the pediatric ward of Hasan Sadikin Hospital.Methods This retrospective study was conducted by reviewingmedical records from 2008-2010. Characteristics of 11 pertussislikesyndrome patients were documented including age, gender,history of pertussis immunization, clinical manifestations,laboratory findings, initial diagnosis, treatment and clinicalresponse. Isolation of Bordetella pertussis using Bordet-Gengouagar was also noted. Pertussis diagnoses were grouped based ontwo classifications: probable and confirmed.Results Eleven patients were diagnosed with pertussis-likesyndrome, including 5 boys and 6 girls. Most subjects were lessthan 6 months of age. Only one subject had received previouspertussis immunization. Dyspnea, paroxysmal cough, and feverwere the most common symptoms. All were initially diagnosedto have had severe bacterial pneumonia, and later changed toprobable pertussis. Three subjects exhibited post-tussive vomitingand cyanosis, while none had apneic symptoms. All B. pertussisisolations yielded negative results. Ampicillin or cephalosporinwas initially administered. Patients receiving subsequentclarithromycin showed good clinical responses.Conclusion All infants were likely considered to have pertussis,as most had no pertussis immunizations. However, B. pertussisisolation was unsuccessful in all cases. As such, diagnoses couldnot be confirmed. [Paediatr In don es. 2012;5 2: 28-31].